2018
DOI: 10.1177/105268461802800303
|View full text |Cite
|
Sign up to set email alerts
|

Looking behind the Curtain

Abstract: This article extends mixed-methods longitudinal research with school and district leaders (2008–present) about their most pressing leadership challenges. Here—through in-depth, qualitative interviews—we explore how a subsample of 30 principals described and understood their internal experiences of addressing pressing challenges. More specifically, using an adaptive/ technical lens, social-emotional frameworks, and constructive-developmental theory, we illuminate how principals‘ social-emotional and development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Principals face enormous implicit and explicit complexities in their work as they are required to deal with a variety of issues, such as distributing leadership, supporting everyone in their school community, adapting the Common Core and new evaluation systems and much more, all within accountability and sanction-driven context (Drago-Severson et al, 2018). Thus, managing multiple responsibilities and working under increasingly stressful conditions can result in lower levels of job satisfaction, increased occupational stress and burnout (Salmela-Aro et al, 2019) and have an impact on their occupational and overall well-being (Collie et al, 2020;Darmody and Smyth, 2016;Elomaa et al, 2021).…”
Section: Overview Of Principals' Practicesmentioning
confidence: 99%
See 4 more Smart Citations
“…Principals face enormous implicit and explicit complexities in their work as they are required to deal with a variety of issues, such as distributing leadership, supporting everyone in their school community, adapting the Common Core and new evaluation systems and much more, all within accountability and sanction-driven context (Drago-Severson et al, 2018). Thus, managing multiple responsibilities and working under increasingly stressful conditions can result in lower levels of job satisfaction, increased occupational stress and burnout (Salmela-Aro et al, 2019) and have an impact on their occupational and overall well-being (Collie et al, 2020;Darmody and Smyth, 2016;Elomaa et al, 2021).…”
Section: Overview Of Principals' Practicesmentioning
confidence: 99%
“…Darmody and Smyth (2016) found job satisfaction and occupational stress to be related to a complex set of personal characteristics, working conditions and school context. The personal characteristics influencing principals' work might be, for example, gender, age and length of service (Darmody and Smyth, 2016), health concerns (Elomaa et al, 2021) and internal dimensions of leadership (how a leader feels about the school, colleagues and themselves) (Drago-Severson et al, 2018). In addition, Leithwood and colleagues (2020) found that a set of cognitive (problem-solving expertise, domain-specific knowledge, systems thinking), social (perceiving emotions, managing emotions, acting in emotionally appropriate ways) and psychological (optimism, self-efficacy, resilience, proactivity) personal leadership resources can explain a high proportion of the variation in leadership effectiveness.…”
Section: Overview Of Principals' Practicesmentioning
confidence: 99%
See 3 more Smart Citations